2014
DOI: 10.4187/respcare.03165
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of an Internet-Based Program to Promote Physical Activity in Adults With Cystic Fibrosis

Abstract: BACKGROUND: Lifelong physical activity is an important component of the therapeutic management of patients with cystic fibrosis (CF). Use of the internet to monitor and encourage participation in physical activity has not been assessed in adults with CF. We aimed to establish the feasibility and acceptability of a specifically developed internet-based program to monitor and encourage physical activity participation in adults with CF. METHODS: Subjects were recruited at hospital discharge to trial an internet-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…Of the articles reporting visualization-specific findings, many reported that visualizations were generally well liked by patients and considered valuable. [49][50][51] Visualizations helped patients to ask more sophisticated clinical questions, identify relationships over time, and articulate specific health concerns. 52,53 The level of support for patient comprehension of different visualization types varied between studies.…”
Section: Characteristics Of Articles With Human Patients Researchmentioning
confidence: 99%
“…Of the articles reporting visualization-specific findings, many reported that visualizations were generally well liked by patients and considered valuable. [49][50][51] Visualizations helped patients to ask more sophisticated clinical questions, identify relationships over time, and articulate specific health concerns. 52,53 The level of support for patient comprehension of different visualization types varied between studies.…”
Section: Characteristics Of Articles With Human Patients Researchmentioning
confidence: 99%
“…Delivering exercise programs via telehealth using video-conferencing may provide an alternative way to enable stroke survivors to engage in supervised exercise at home. Telehealth exercise interventions targeting fitness have proved effective and safe in other populations, including cardiac rehabilitation (Clark et al, 2015), chronic obstructive pulmonary disease (Hwang et al, 2015), cystic fibrosis (Cox, Alison, Button, Wilson, & Holland, 2015) and in the elderly (Crotty et al, 2014), and telehealth is emerging as a cost-effective alternative to providing centre-based exercise programs (Maddison et al, 2018;Southard, Southard, & Nuckolls, 2003;Whittaker & Wade, 2014). In stroke, telehealth has been used successfully to monitor vital signs (Bernocchi et al, 2016), motor recovery, depression and higher cortical function (Sarfo, Ulasavets, Opare-Sem, & Ovbiagele, 2018), and to deliver speech pathology (Hill et al, 2006), upper limb physiotherapy (Benvenuti et al, 2014) and rehabilitation exercises (Bernocchi et al, 2016).…”
mentioning
confidence: 99%
“…Finally, apart from staffing, one of the main limitations to implementing an outpatient exercise training programme was related to the risk of cross‐infection between people with CF. Considering emerging methods of exercise testing and training supervision, such as telehealth, which was reported in one centre, is likely to be an important alternative to reduce the risk of cross infection.…”
Section: Discussionmentioning
confidence: 99%